2013
DOI: 10.4240/wjgs.v5.i4.83
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-based diagnostics might be insufficient in the determination of pancreatic cancer unresectability

Abstract: Arterial encasement on CT does not necessarily indicate arterial invasion. Whenever PC is considered unresectable, endoUS should be used. In patients with controversial CT an EUS data for peripancreatic arteries involvement radical resection might be possible, providing survival benefits as compared to R2- resections or palliative surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Assessment of vascular invasion is the key in the evaluation of resectability for pancreatic cancer. 2 Surgical exploration with pathological examination remains the "gold standard" in terms of evaluation of resectability, especially from the point of view of vascular involvement. Unresectability in pancreatic adenocarcinoma is encasement of the superior mesenteric and celiac arteries, indicating vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of vascular invasion is the key in the evaluation of resectability for pancreatic cancer. 2 Surgical exploration with pathological examination remains the "gold standard" in terms of evaluation of resectability, especially from the point of view of vascular involvement. Unresectability in pancreatic adenocarcinoma is encasement of the superior mesenteric and celiac arteries, indicating vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of vascular invasion is the key in the evaluation of resectability for pancreatic cancer. 2 Loyer et al noted that the presence of a fat plane between tumour and vesses is agood prognostic sign of resectability. 3 Phoa et al noted that in vessel embedment into tumour or vessel's circular encasement, the rate of vessel invasion was 88% and resectability 7%.…”
Section: Introductionmentioning
confidence: 99%
“…Tadros and, Remon Zaher Elia (2016) showed Liver metastases were detected by 7 patients (50%),ascites in 2 patients (14%) and Osteolytic bony lesions were found in (7%). (23) Assessment of vascular invasion is an important parameter for determining resectability of pancreatic cancer (26) In their study, Vyacheslav I Egorov et al found vascular involvement of patients with pancreatic carcinoma ranges between (21%-64%), most often with involvement of SMA, due to its location (27) . In our study, 8 patients (44.4%) showed a vascular involvements, among them SMA and splenic artery were the most involved arteries, while SMV and splenic vein were the most involved veins.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…Determination of tumour resectability is a major aspect of the interpretation of pre-operative imaging of peri-ampullary cancer (PC). The findings of distant metastases and local invasion resulting in occlusion of major arteries or veins are contraindications to attempted surgical resection, whereas lesser degrees of arterial involvement (AI) and venous involvement (VI), including abutment and tapering, are relative contraindications, as imaging can sometimes be inaccurate in determining these findings (1)(2)(3)(4), and vein resection can be undertaken where incomplete venous occlusion is noted (5)(6)(7). Tumour size (8) and regional lymphadenopathy (RL) (9,10) have also been shown to be associated with unresectability, although RL is a relative contraindication as these nodes are removed as part of a Whipple procedure (11).…”
Section: Introductionmentioning
confidence: 99%